Cardiovascular and arousal responses to single-lumen endotracheal and double-lumen endobronchial intubation in the normotensive and hypertensive elderly - Kyung Yeon Yoo (Korean Journal of Anesthesiology, 2011)
BackgroundEndotracheal intubation usually causes transient hypertension and tachycardia. The cardiovascular and arousal responses to endotracheal and endobronchial intubation were determined during rapid-sequence induction of anesthesia in normotensive and hypertensive elderly patients.MethodsPatients requiring endotracheal intubation with (HT, n = 30) or without hypertension (NT, n = 30) and those requiring endobronchial intubation with (HB, n = 30) or without hypertension (NB, n = 30) were included in the study. Anesthesia was induced with intravenous thiopental 5 mg/kg followed by succinylcholine 1.5 mg/kg. After intubation, all subjects received 2% sevoflurane in 50% nitrous oxide and oxygen. Mean arterial pressure (MAP), heart rate (HR), plasma catecholamine concentration, and Bispectral Index (BIS) values, were measured before and after intubation.ResultsThe intubation significantly increased MAP, HR, BIS values and plasma catecholamine concentrations in all groups, the peak value of increases was comparable between endotracheal and endobronchial intubation. However, pressor response persisted longer in the HB group than in the HT group (5.1 ± 1.6 vs. 3.2 ± 0.9 min, P < 0.05). The magnitude of increases in MAP and norepinephrine from pre-intubation values was greater in the hypertensive than in the normotensive group (P < 0.05), while there were no differences in those of HR and BIS between the hypertensive and normotensive groups.ConclusionsCardiovascular response and arousal response, as measured by BIS, were similar in endobronchial and endotracheal intubation groups regardless of the presence or absence of hypertension except for prolonged pressor response in the HB group. However, the hypertensive patients showed enhanced cardiovascular responses than the normotensive patients.